Spectroscopic, thermodynamic and computational evidence of the locations of the FADs in the nitrogen fixation-associated electron transfer flavoprotein. Issue 33 (8th July 2019) - Mohamed-Raseek, Nishya; Duan, H. Diessel; Hildebrandt, Peter; Mroginski, Maria Andrea; Miller, Anne-Frances
Abstract : Experiments and computation establish the locations of the two flavins whose contrasting reactivities produce electron bifurcation in ETFs. They confirm the accepted model and support homologies & distinctions between bifurcating and canonical ETFs. Abstract : Flavin-based electron bifurcation allows enzymes to redistribute energy among electrons by coupling endergonic and exergonic electron transfer reactions. Diverse bifurcating enzymes employ a two-flavin electron transfer flavoprotein (ETF) that accepts hydride from NADH at a flavin (the so-called bifurcating FAD, Bf-FAD). The Bf-FAD passes one electron exergonically to a second flavin thereby assuming a reactive semiquinone state able to reduce ferredoxin or flavodoxin semiquinone. The flavin that accepts one electron and passes it on via exergonic electron transfer is known as the electron transfer FAD (ET-FAD) and is believed to correspond to the single FAD present in canonical ETFs, in domain II. The Bf-FAD is believed to be the one that is unique to bifurcating ETFs, bound between domains I and III. This very reasonable model has yet to be challenged experimentally. Herein we used site-directed mutagenesis to disrupt FAD binding to the presumed Bf site between domains I and III, in the Bf-ETF from Rhodopseudomonas palustris ( Rpa ETF). The resulting protein contained only 0.80 ± 0.05 FAD, plus 1.21 ± 0.04 bound AMP as in canonical ETFs. The flavin was not subject to reduction by NADH, confirming absence of Bf-FAD. The retained FAD displayed visible circular dichroism (CD) similar to that of the ET-FAD of Rpa ETF. Likewise, the mutant underwent two sequential one-electron reductions forming and then consuming anionic semiquinone, reproducing the reactivity of the ET-FAD. These data confirm that the retained FAD in domain II corresponds the ET-FAD. Quantum chemical calculations of the absorbance and CD spectra of each of WT Rpa ETF's two flavins reproduced the observed differences between their CD and absorbance signatures. The calculations for the flavin bound in domain II agreed better with the spectra of the ET-flavin, and those calculated based on the flavin between domains I and III agreed better with spectra of the Bf-flavin. Thus calculations independently confirm the locations of each flavin. We conclude that the site in domain II harbours the ET-FAD whereas the mutated site between domains I and III is the Bf-FAD site, confirming the accepted model by two different tests.